Nathaniel Rochester papers - Rochester, Nathaniel
Correspondence, biographical material, oral history interviews, reports, writings, data processing manuals, printed matter, photographs, and other papers primarily documenting Rochester's work with military radar at the Sylvania Electric Products and his design of computers and computer programs at the International Business Machines Corporation (IBM). Includes tube technical data, a circuit theory notebook, and manuals about the 705 and 709 computers and COBOL and APL computer languages. Also includes material pertaining to Rochester's work on radar at the Massachusetts Institute of Technology and the final report of a task force on which he served to develop the first air traffic control system in 1961.
Electrical engineer and computer designer. Born 1919; died 2001.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: International Business Machines Corporation; Massachusetts Institute of Technology; Sylvania Electric Products, Inc; Air traffic control; APL (Computer program language); COBOL (Computer program language); Computer engineering; Computer software -- Development; Computers; Programming languages (Electronic computers); Radar; Radar -- Military applications; Engineers